Implementation of resource recovery practices among Malaysian construction stakeholders - Wan Nadzri Osman; Mohd Nasrun Mohd Nawi (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Most of the construction stakeholders around the world especially in developing countries are not really aware of the Resource Recovery approaches in contemporary construction projects. Previous studies reported that Resource Recovery issues received less attention from the construction industry stakeholders compared to construction costs and time related issues. However, this trend has changed due to the depletion of non-renewable resources, greenhouse gas emissions and global warming with much effort now being directed to ‘build greener’ construction projects through proper application of the Resource Recovery approach. This study examined current application of Resource Recovery approach among Malaysia’s construction stakeholders. Primary data were gathered from 122 questionnaires returned by Malaysian construction stakeholders that included consultants, contractors and clients . The analysis revealed that the adoption of Resource Recovery was only mildly practiced by the Malaysian construction stakeholders.